Socio economic profile of women dairy farmers in Krishna district of Andhra Pradesh (Indian Journal of Animal Production and Management, 2024)
An investigation was conducted to study the socio-economic profile of 225 dairy farm women Krishna  district of Andhra Pradesh. The study revealed that majority of the women belonged to middle age group  (68%), other caste (54.22%) and had primary education (36.44%). Most of them were married (95.11%),  belonged to nuclear families (73.33%) and had small family size (67.11%). Agricultural farming and dairying  was the major occupation (52.88%) of women in the study area. Most of the women had medium level  of experience in dairying (46.66%). Only 8% of women dairy farmers had exposure to training related to  dairying, 73.77% of them are members in DWCRA/SHG and only 19.55% are members in cooperative  societies. Majority of women dairy farmers were occasionally in contact with veterinarian (45.77%), para  veterinarian (38.66%), friends and relatives (71.55%). Women under the medium farmer category were  more exposed to television (50.66%), news paper (17.33%) and farm magazine (14.66%) compared to  landless and small farmer category. Small farm women (587.00±81.70) obtained more income (rupees/ day) through dairying followed by medium (516.34±54.35) and landless (385.66±32.39) farm women.
Keywords: Socio economic profile; dairy farming women; Krishna district; Andhra Pradesh